A successful learning environment for biology teachers in higher education: Needs assessment - Labak, Irena; Blazetic, Senka (Journal of Education and e-Learning Research, 2023)
Teachers must enhance their teaching skills in accordance with institutional policies at higher education institutions. This research aims to determine effective professional development techniques for biology teachers in higher education. The modified OZON form (cro. obrazac za opažanje nastave, teaching observation form) facilitated self-reflection and assessed the impact of reflection-based actions on the learning environment. Teachers participated in workshops, experiencing both student and curriculum-designer roles. Proficiency in creating an engaging learning environment and using technology was well developed. However, teachers should improve their understanding of curricular aspects, constructive alignment, outcome-driven selection of activities and formative and summative evaluation. Our research suggests modifying professional learning strategies to align with biology teachers’ needs in higher education. Combining extended learning time, implementation in teaching practice, ongoing expert support, and action research fosters positive changes in a constructively aligned classroom. The results indicate that biology teachers in higher education need the continuous support of experts in the didactic design of the lesson plan to improve the creation of a learning environment through positive alignment. This approach promotes active professional development management in a concise format.